Fucosylated exosomal miRNAs as promising biomarkers for the diagnosis of early lung adenocarcinoma - Chen, Xiongfeng; Yu, Lili; Hao, Kun; Yin, Xiaoqing; Tu, Mingshu; Cai, Liqing; Zhang, Liangming; Pan, Xiaojie; Gao, Qi; Huang, Yi (Frontiers in Oncology, 2022)
Background Considering the absence of apparent symptoms at the early stage, most patients with lung adenocarcinoma (LUAD) present at an advanced stage, leading to a dismal 5-year survival rate of <20%. Thus, finding perspective non-invasive biomarkers for early LUAD is very essential. Methods We developed a fucose-captured strategy based on lentil lectin-magnetic beads to isolate fucosylated exosomes from serum. Then, a prospective study was conducted to define the diagnostic value of serum exosomal miRNAs for early LUAD. A total of 310 participants were enrolled, including 146 LUAD, 98 benign pulmonary nodules (BPNs), and 66 healthy controls (HCs). Firstly, exosome miRNAs in the discovery cohort (n = 24) were profiled by small RNA sequencing. Secondly, 12 differentially expressed miRNAs (DEmiRs) were selected for further screening in a screening cohort (n = 64) by qRT-PCR. Finally, four candidate miRNAs were selected for further validation in a validating cohort (n = 222). Results This study demonstrated the feasibility of a fucose-captured strategy for the isolation of fucosylated exosomes from serum, evidenced with exosomal characteristics identified by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Western blotting, as well as rapid and convenient operation of <10 min. Furthermore, a miRNA panel for early LUAD composed of miR4732-5p, miR451a, miR486-5p, and miR139-3p was defined with an AUC of 0.8554 at 91.07% sensitivity and 66.36% specificity. Conclusions The fucose-captured strategy provides a reliable, as well as rapid and convenient, approach for the isolation of tumor-derived exosomes from serum. A four-fucosylated exosomal miRNA panel presents good performance for early LUAD diagnosis.